Paleoenvironmental conditions during deposition of Kolosh and Gercus formations in northern Iraq as deduced from clay mineral distributions - Al-Juboury, Ali Ismail; Al-Taee, Noor Talal; Malak, Zaid A. (Iraqi Journal of Science, 2021)
A mineralogical study using X-ray diffraction supported by scanning electron microscopic examination on the Paleocene- Eocene Kolosh and Gercus formations from northern Iraq is conducted to show the distribution of clay minerals and their paleoenvironmental implications. Smectite palygorskite, kaolinite, illite, and chlorite are commonly present in varying proportions within the Kolosh and Gercus formations. Association of smectite and chlorite in the claystone of the Paleocene Kolosh Formation refers to marine environment of this formation, whereas development of palygorskite fibers from smectite precursor may relate to post-depositional diagenesis. In addition, the abundance of illite and kaolinite in the Eocene Gercus Formation suggests a greater influence of terrigenous input in humid conditions, affecting the distribution of these clay minerals. The study shows vertical change in clay minerals distribution when illite and kaolinite dominate in the Eocene Gercus Formation, in comparison to chlorite and smectite abundance in the Paleocene Kolosh Formation which may relate to global warming in the Eocene.